The Design Museum of Mount Sinabung with Neo-Vernacular Architecture Approach - Wahyuni Zahrah; Ade Syahputra Astono (Talenta Publisher, 2019)
Mount Sinabung is a volcano on the plateau of Karo Regency, North Sumatra, Indonesia. Mount Sinabung suddenly erupted in 2010. The last eruption of the volcano occurred since February 19, 2018, and until now become an attraction to find out more about volcanic disasters. Museum Mount Sinabung is present to provide the means for education, dissemination of information in the aspect of the volcano and geological disaster with recreative and educative of nature. The problem raised was